The Improvement of Art Exhibition Quality Through Teaching Materials Development for the Management of Art Exhibition - Osberth Sinaga; Daulat Saragi; Ibrahim Anam (Universitas Negeri Medan, 2023)
This research is aimed to create teaching materials for art exhibition management in order to improve the implementation and management of art exhibitions. This is a research and development using the 4D model: define, design, develop, and disseminate. The instrument of this research used is a questionnaire that consists of validator questionnaire, design material and language as well as the college students’ response questionnaire as input in revising the developed teaching materials. The results of this study indicate that the teaching materials developed by the researchers are in the very good category so they are worth to be tried out. At the testing stage, the developed teaching materials were in the very good category. The response from exhibition visitors has also increased. For that reasons, the teaching materials that researchers developed can improve the art exhibitions quality.